2013
DOI: 10.1038/ncomms3239
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial assembly of protein–polymer nano-conjugates into stimulus-responsive biomimetic protocells

Abstract: The mechanism of spontaneous assembly of microscale compartments is a central question for the origin of life, and has technological repercussions in diverse areas such as materials science, catalysis, biotechnology and biomedicine. Such compartments need to be semipermeable, structurally robust and capable of housing assemblages of functional components for internalized chemical transformations. In principle, proteins should be ideal building blocks for the construction of membrane-bound compartments but prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
447
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 465 publications
(450 citation statements)
references
References 43 publications
0
447
0
3
Order By: Relevance
“…We have searched the available literature for references to similar membrane protein assemblies, and we have not been able to find any previously recorded discoveries of this particular type. We did find a designed synthetic protein/polymer assembly reported by Huang et al (27) that produced ordered vesicle structures, which they termed "proteinosomes," to describe protein-polymer assembled compartments. We believe this term can also be applied to the MmsF, MamF, and MmxF structures.…”
Section: Discussionmentioning
confidence: 97%
“…We have searched the available literature for references to similar membrane protein assemblies, and we have not been able to find any previously recorded discoveries of this particular type. We did find a designed synthetic protein/polymer assembly reported by Huang et al (27) that produced ordered vesicle structures, which they termed "proteinosomes," to describe protein-polymer assembled compartments. We believe this term can also be applied to the MmsF, MamF, and MmxF structures.…”
Section: Discussionmentioning
confidence: 97%
“…M olecular self-assembly is of importance in the fabrication of uniformly patterned functional surfaces, membranes and delivery vehicles, including hydrogels and microcapsules 1,2 . The self-assembly of molecular monolayers can be readily accomplished at a variety of interfaces, including metal (for example, gold), metal oxide substrates (for example, silica) or at an air-water interface, to form self-assembled monolayers [3][4][5][6] .…”
mentioning
confidence: 99%
“…36,37 Double nanocapsules designed to encapsulate proteins in their separated microsphere structures can protect the structural and functional integrities of proteins when they are transported into the cytosol and then redistributed within the cells. [38][39][40] Besides the transport of BSA into the cytosol, the study showed that the nanocapsules delivered NLS-GFP into the nucleus, indicating that the structure of nanocapsules did not interfere with the migration of proteins.…”
Section: Discussionmentioning
confidence: 99%